POLEMIK PEMIDANAAN (Kontroversi Faham Abolisionis Dan Retensionis) - Risman Risman (Jurnal Syariah Hukum Islam, 2018)
The existence of imprisonment in the present is a sharp spotlight from various circles. Some experts have initiated the abolition of imprisonment because they are considered outdated and are not in accordance with modern human rights. On the other hand, some consider that imprisonment is still viable as an alternative to tackling crime with certain assumptions and justifications. The debate and controversy between the two abolitionist and retentionist camps has increasingly found its place if it is associated with the current fact that the criminal justice system only demonstrates its success in convicting, the justice system cannot be an instrument to restore one's humanity.